SUSTAINABLE FINANCE AND GREEN BANKING DISCLOSURE: UNLOCKING FIRM VALUE POTENTIAL - Puspitasari, Adelia; Firmansyah, Amrie (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
This research examines the impact of green banking disclosure and sustainable finance on firm value, with institutional ownership as a moderating element. The data utilized are secondary data acquired from the annual and sustainability reports of banking firms listed on the Indonesia Stock Exchange from 2019 to 2023. The research used a purposive selection technique encompassing 12 banking institutions, yielding 60 observation units. Panel data regression analysis is performed utilizing STATA version 17 software. The results indicate that green banking disclosure does not substantially influence firm value, whereas sustainable finance favors firm value. Moreover, institutional ownership does not enhance the positive correlation between green banking disclosure and firm value but diminishes the positive correlation between sustainable finance and firm value. This work theoretically enhances the comprehension of green banking transparency, sustainable finance, and firm value interplay. The findings provide essential insights for banking institutions to augment openness in sustainability reporting and act as an assessment instrument for regulators, including the Financial Services Authority, to refine rules concerning sustainable financing.